Urethral obstruction in a male Brazilian Short Hair feline without surgical intervention: Case report - Castro, Karina Bezerra de; Vasconcelos, Thereza Christina de (Pubvet, 2024)
This study aimed to report a clinical case of a male feline diagnosed with urethral obstruction that underwent conservative treatment without surgical intervention. In the present report, the three-year-old, male, orchiectomized feline was diagnosed with urethral obstruction, also called urinary tract disease, which is a urological disease in the emergency veterinary clinical routine of small animals, being more common in felines, and either partial or total. This pathology can be caused by crystals, uroliths, neoplasms and granulomas, but it can also be related to inadequate food management, lack of environmental enrichment, or simply be an idiopathic disease. Symptoms are non-specific, which makes diagnosis difficult, and possible clinical signs may include hematuria, dysuria, pruriria, urinary frequency, acute stranguria, which may become chronic or intermittent. However, the animal usually presents excessive vocalization, pain and discomfort during micturition. The diagnosis is carried with radiographic examination to assess cardiopulmonary parameters and ultrasound examination to assess real-time information on the architecture of the abdominal organs and laboratory tests that describe all changes in the erythrogram, global leucometry, platelets and parameters of substances that assess renal function. Treatment depends on the frequency of obstruction and the animal's response to conservative treatment. Surgical intervention, which consists of perineal urethrostomy associated with penectomy, is indicated for cases of recurrent urethral obstruction or when conservative treatment fails. Conservative treatment, which includes environmental enrichment and dietary management, is an option for non-recurrent urethral obstructions. Environmental enrichment (water sources, wet food offered several times a day, frequently replenishing water sources to encourage an increase in water intake, litter boxes around the house - always double the number of cats - scratching posts that allow the cat to deposit its scent through the glands present in its paw, pheromones to reduce anxiety), that is, everything aimed solely at the well-being of the domiciled feline, tends to improve their quality of life, interactions with household members, and reduce recurrent relapses of the obstructive condition, obesity, and comorbidities associated with this pathology.
Keywords: Environmental enrichment; neutered; penectomy; perineal urethrostomy; urination